Effect of Itraconazole or Rifampin on Itacitinib Pharmacokinetics When Administered Orally in Healthy Subjects. (8th July 2019) - Barbour, April M.; Punwani, Naresh; Epstein, Noam; Landman, Robert; Cimino, Evan; Yuska, Brad; Wang, Phillip; He, Kevin; Chen, Xuejun; Yeleswaram, Swamy
Abstract: Itacitinib is a potent, selective JAK‐1 inhibitor currently in phase 3 development for the treatment of acute and chronic graft‐versus‐host disease (GVHD) in combination with corticosteroids. Itacitinib is primarily eliminated via metabolism by cytochrome P‐450 (CYP)3A4 with minimal renal elimination. A drug‐drug interaction study was conducted to evaluate the impact of the strong CYP3A inhibitor itraconazole or the strong CYP3A4 inducer rifampin on the pharmacokinetics of itacitinib in healthy volunteers. In cohort 1, subjects received 200 mg sustained release (SR) tablets of itacitinib on days 1 and 6 and 200 mg itraconazole on days 2‐7. In cohort 2, subjects received 200 mg SR itacitinib on days 1 and 9 and 600 mg rifampin on days 2‐9. Thirty‐six subjects were enrolled, 18 in each cohort with 17 completing itacitinib dosing in cohort 1 and 15 completing itacitinib dosing in cohort 2. Coadministration of itraconazole with itacitinib resulted in a nearly 5‐fold increase in area under the concentration‐time curve (AUC0‐∞ ) (geometric mean ratio [GMR] 4.88, 90%Cl 4.17‐5.72) and an ∼3‐fold increase in peak concentration (Cmax ) (GMR 3.15, 90%Cl 2.58‐3.54). Coadministration of rifampin with itacitinib resulted in a nearly 80% decrease in AUC0‐∞ (GMR 0.208, 90%Cl 0.173, 0.249) and Cmax (GMR 0.231, 90%Cl 0.195, 0.274). Results of this study informed the study design of the phase 3 GVHD protocols with regard to coadministration of strong CYP3A inhibitors and CYP3A4 inducers. These data combined with phase 3 data will inform final dosing recommendations.